STRESS-testing clinical activity and outcomes for a combined prison in-reach and court liaison service: a 3-year observational study of 6177 consecutive male remands. Issue 1 (December 2016) - O'Neill, Conor; Smith, Damian; Caddow, Martin; Duffy, Fergal; Hickey, Philip; Fitzpatrick, Mary; Caddow, Fintan; Cronin, Tom; Joynt, Mark; Azvee, Zetti; Gallagher, Bronagh; Kehoe, Claire; et al.
Abstract Background People with major mental illness are over-represented in prison populations however there are few longitudinal studies of prison in-reach services leading to appropriate healthcare over extended periods. Aims We aimed to examine measures of the clinical efficiency and effectiveness of a prison in-reach, court diversion and liaison service over a 3 year period. Secondly, we aimed to compare rates of identification of psychosis and diversion with rates previously reported for the same setting in the 6 years previously. We adopted a stress testing model for service evaluation. Method All new male remand committals to Ireland's main remand prison from 2012 to 2014 were screened in two stages. Demographic and clinical variables were recorded along with times to assessment and diversion. The DUNDRUM Toolkit was used to assess level of clinical urgency and level of security required. Binary logistic regression was used to assess factors relevant to diversion. Results All 6177 consecutive remands were screened of whom 1109 remand episodes (917 individuals) received a psychiatric assessment. 4.1 % (95 % CI 3.6–4.6) had active psychotic symptoms. Levels of self-harm were low. Median time to full assessment was 2 days and median time to admission was 15.0 days for local hospitals and 19.5 days for forensic admissions. Diversion to healthcare settings outside prison was achieved for 5.6 % (349/6177, 95 % CI 5.1–6.3) of all remand episodes and admissions for 2.3 % (95 % CI 1.9–2.7). Both were increased on the previous period reported. Mean DUNDRUM-1 and DUNDRUM-2 Triage Security Scores were appropriate to risk and need. Conclusions We found that a two-stage screening and referral process followed by comprehensive assessment optimised identification of acute psychosis. The mapping approach described shows that it is possible for a relatively small team to sustainably achieve effective identification of major mental illness and diversion to healthcare in a risk-appropriate manner. The stress-testing structure adopted aids service evaluation and may help advise development of outcome standards for similar services.